Isolated bangla handwritten character & digit recognition using convolutional neural network - Alif, Mujadded Al Rabbani; Ahmed, Sabbir; Aninda, Aleo; Das, Tanoy Kumar (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.